Kritik Sastra Feminis dalam Komik Kaich? wa Meido-Sama! Karya Hiro Fujiwara - Yani Anggarawati, Made; Damayanti, Silvia; Andry Anita Dewi, Ni Made (Humanis; Vol 24 No 1 (2020)DO - 10.24843/JH.2020.v24.i01.p13, 2020)
The title of this research is “The Feminist Literary Criticism in Kaich? wa Meido-Sama! by Hiro Fujiwara”. This research focuses on two problems: how the feminism is shown in Kaich? wa Meido-Sama! by Hiro Fujiwara and how is the main character’s feminism ideology influence another character in the comic. Methods used in this research is descriptive analysis method and the informal method. The theories used are feminism theory by Lorber (1997) and semiotics by Danesi (2011). The analysis result shows that feminisms ideology that revealed in the comics is liberal feminism, such as women also can be physically strong, rational and using men’s language; women as a leader; women were not inferior; and social discrimination against women. Liberal feminism ideology of the main character has positive and negative influences to another character in the comic. The positive influences show on some attitudes from characters such as Shotaro Kano and Tora Igarashi towards women and also female and male students relation. The negative influence shows in the dependence female students on the female character, Misaki Ayuzawa.